Electrospun aniline-tetramer-co-polycaprolactone fibres for conductive, biodegradable scaffolds - Guex,AG; Spicer,CD; Armgarth,A; Gelmi,A; Humphrey,EJ; Terracciano,CM; Harding,S; Stevens,MM (MRS Communications, 2017)
Conjugated polymers have been proposed as promising materials for scaffolds in tissue engineering applications. However, the restricted processability and biodegradability of conjugated polymers limit their use for biomedical applications. Here we synthesized a block-co-polymer of aniline tetramer and PCL (AT–PCL), and processed it into fibrous non-woven scaffolds by electrospinning. We showed that fibronectin (Fn) adhesion was dependent on the AT–PCL oxidative state, with a reduced Fn unfolding length on doped membranes. Furthermore, we demonstrated the cytocompatibility and potential of these membranes to support the growth and osteogenic differentiation of MC3T3-E1 cells over 21 days.